Target costing: adoption and its relationships with competition intensity, intended strategy and firm size / Helmi Hammami ...[et al.] - Hammami, Helmi; Al-Omiri, Mohammed; Bouraoui, Taoufik; Anam, Ousama Abdulrahman (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2019)
The paper aims to examine the level of the adoption of the target costing (TC) system by Saudi manufacturing companies and its relationships with competition intensity, intended strategy and firm size. The paper used a questionnaire survey to measure the adoption of TC and the effect of competition intensity and intended strategy on this adoption. Descriptive statistic and regression analysis were preformed to analyse the data and obtain the results. This study found that Saudi manufacturing companies were interested to adopt the TC system. In addition, it found that the competition intensity positively affects TC adoption. Moreover, the study found that companies that used a differentiation strategy were more inclined to adopt the TC than those that used a cost leadership strategy. Finally, it found that large manufacturing companies tend to adopt TC more than small ones. This is among the pioneer studies to study the TC system in Saudi Arabia, introducing a new area of investigation. Moreover, the study contributes to managerial accounting research in developing economies by providing new insights into the underexplored Saudi Arabia market. The findings of this paper could elucidate the importance of adoption of TC as a technique with a potential to support the economic growth of the country.